Experience of using Rituximab in neurological practice (literature review and own observation) - Ya. B. Kushnir; N. M. Tereshchenko; M. P. Abramova; A. A. Gotovchikov; A. Yu. Polushin; V. S. Krasnov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
Currently, due to the lack of specific etiotropic therapy, rituximab is widely used for the treatment of most autoimmune diseases of the central and peripheral nervous system. Rituximab is a chimeric monoclonal antibody with specificity for CD20, the antigen found on the surface of normal and malignant B-lymphocytes. It is used mainly in hematological practice. It is used off-label for the treatment of neurological diseases. The world literature describes the use of rituximab for the treatment of such pathologies as autoimmune encephalitis, neuromyelitis optica spectrum disorder, multiple sclerosis, primary angiitis of the central nervous system, immune-mediated inflammatory polyneuropathy, myasthenia gravis, refractory to basic immunosuppressive therapy. This article provides an overview of the world literature on the use of rituximab in neurological practice, describes our own experience of its use on the basis of the Department of Neurology № 1 of Pavlov University (Saint Petersburg, Russia).